Fabrication of high-performance symmetrical coin cell supercapacitors by using one step and green synthesis sulfur doped graphene powders - Arvas, Melih Besir; Karatepe, Nilgun; Gencten, Metin; Sahin, Yucel (ROYAL SOC CHEMISTRY, 2021)
In this work, symmetrical supercapacitors in the form of coin cell types were produced by using S-doped graphene powders. Sulfur doped graphene powders were prepared by cyclic voltammetry in different potential ranges for selective modification of powders by functional groups. S-Doped graphene powders were also characterized by spectroscopic, microscopic, and electrochemical methods. The formation of graphene layers was supported by scanning electron microscopic and Raman spectroscopic analyses. Functional groups formed on the graphene surface were identified by X-ray photoelectron spectroscopy. The electrodes formed with compositions consisting of binding material at 5%, conductive material at 5% and S-doped graphene powder at 90% were used in cyclic charge-discharge tests of the supercapacitors to determine the specific capacitance of them. The highest specific capacitance of the supercapacitors was determined as 176 F/g(-1), with a capacity loss of 5% at the end of 1000 cycles in A-SG3M.
Keywords: ULTRAHIGH VOLUMETRIC CAPACITANCE; PENCIL GRAPHITE-ELECTRODES; OXYGEN REDUCTION REACTION; LITHIUM-ION; POTENTIAL APPLICATION; COMPOSITE-MATERIALS; CYCLIC VOLTAMMETRY; RAMAN-SPECTROSCOPY; ROOM-TEMPERATURE; ANODE MATERIALS; Chemistry